The [C ii] emission as a molecular gas mass tracer in galaxies at low and high redshifts. Issue 2 (3rd September 2018) - Zanella, A; Daddi, E; Magdis, G; Diaz Santos, T; Cormier, D; Liu, D; Cibinel, A; Gobat, R; Dickinson, M; Sargent, M; Popping, G; Madden, S C; et al.
ABSTRACT: We present ALMA Band 9 observations of the [C ii ]158 $\mu$ m emission for a sample of 10 main-sequence galaxies at redshift $z$  ∼ 2, with typical stellar masses (log  M ⋆ /M⊙  ∼ 10.0–10.9) and star formation rates (∼35–115 M⊙ yr −1 ). Given the strong and well-understood evolution of the interstellar medium from the present to $z$  = 2, we investigate the behaviour of the [C ii ] emission and empirically identify its primary driver. We detect [C ii ] from six galaxies (four secure and two tentative) and estimate ensemble averages including non-detections. The [C ii ]-to-infrared luminosity ratio (${\rm [C\, {\small II}]}$ / L IR ) of our sample is similar to that of local main-sequence galaxies (∼2 × 10 −3 ), and ∼10 times higher than that of starbursts. The [C ii ] emission has an average spatial extent of 4–7 kpc, consistent with the optical size. Complementing our sample with literature data, we find that the [C ii ] luminosity correlates with galaxies' molecular gas mass, with a mean absolute deviation of 0.2 dex and without evident systematics: the [C ii ]-to-H2 conversion factor ($\alpha _{\rm [C\, {\small II}]} \sim 30$ M⊙ /L⊙ ) is largely independent of galaxies' depletion time, metallicity, and redshift. [C ii ] seems therefore a convenient tracer to estimate galaxies' molecular gas content regardless of their starburst or main-sequence nature, and extending to metal-poor galaxies at low and high redshifts. The dearth of [C ii ] emission reported for $z$ > 6–7 galaxies might suggest either a high star formation efficiency or a small fraction of ultraviolet light from star formation reprocessed by dust.